2018
DOI: 10.1007/s12551-018-0409-4
|View full text |Cite
|
Sign up to set email alerts
|

Relating the multi-functionality of cytochrome c to membrane binding and structural conversion

Abstract: Cytochrome c is known as an electron-carrying protein in the respiratory chain of mitochondria. Over the last 20 years, however, alternative functions of this very versatile protein have become the focus of research interests. Upon binding to anionic lipids such as cardiolipin, the protein acquires peroxidase activity. Multiple lines of evidence suggest that this requires a conformational change of the protein which involves partial unfolding of its tertiary structure. This review summarizes the current state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 129 publications
(264 reference statements)
2
55
0
Order By: Relevance
“…The structural changes in cyt c caused by binding to CL-containing membrane that facilitate its ondemand lipid peroxidase activity, remain elusive. As delineated in a recent comprehensive review (Schweitzer-Stenner, 2018), one challenge relates to the fact that the CL-cyt c interaction is modulated strongly by experimental context. There is also a lack of techniques to probe membrane-bound cyt c with atomic resolution.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The structural changes in cyt c caused by binding to CL-containing membrane that facilitate its ondemand lipid peroxidase activity, remain elusive. As delineated in a recent comprehensive review (Schweitzer-Stenner, 2018), one challenge relates to the fact that the CL-cyt c interaction is modulated strongly by experimental context. There is also a lack of techniques to probe membrane-bound cyt c with atomic resolution.…”
Section: Discussionmentioning
confidence: 99%
“…In solution NMR studies, the membrane-bound protein tumbles too slowly to be observable, even though changes in the spectra of soluble protein reveal aspects of the initial membrane interactions (Brown and Wuthrich, 1977;Kobayashi et al, 2016;Mohammadyani et al, 2018). As such, current insight into membrane-bound cyt c is derived from diverse complementary lower-resolution techniques (Schweitzer-Stenner, 2018). These suggest that cyt c can interact with CL via multiple binding sites (Alvarez-Paggi et al, 2017;Schweitzer-Stenner, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is believed that C c is partially unfolded when bound to mitochondrial negatively charged phospholipids, including cardiolipin, which confers peroxidase activity on the metalloprotein . Interestingly, at early stages of apoptosis, cardiolipin‐bound C c selectively catalyzes cardiolipin peroxidation, which contributes to the OMM permeation and leads to the release of C c into the cytosol . Accordingly, it has been suggested that the apoptosis‐inducing form of C c is the membrane‐bound fraction .…”
Section: Canonical Function Of CC In the Electron Transport Chainmentioning
confidence: 99%